CHIKUNGUNYA: Experience in adults emergency. Hospital III Nuestra Señora de la Chiquinquirá. Maracaibo. Venezuela. September-December 2014 - Carmen C Pirela U.; Ana M Rondón; Amelia Barriga; Olga Zambrano (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
This work reports experience in probable cases of chikungunya fever at adult emergency in a Maracaibo Hospital, Venezuela. It is describes morbidity and mortality between September to December 2014, as well as analysis and clinic diagnosis in acute and complicated cases in a endemic dengue fever zone.